Psychological pain and suicidal behavior: A review - Baryshnikov, Ilya; Isometsä, Erkki (Frontiers in Psychiatry, 2022)
Despite accumulation of clinical research on risk factors for suicidal process, understanding of the mechanisms and pathways underlying the emergence of suicidal thoughts and their progression to acts is insufficient. The suicidal process has been conceptualized in multiple psychological theories that have aimed to shed light on the interplay of contributing factors. One of the central concepts included in both the cubic model of suicide and the three-step theory of suicide is psychological pain (mental pain or psychache). Over the two last decades, interest in psychological pain has increased considerably, particularly since the discovery of the complex link between the pain processing system and the neurobiology of suicide, and the putative antisuicidal effect of buprenorphine. Growing evidence supports the association between experiencing psychological pain and suicidal ideation and acts in both clinical and non-clinical samples. However, many questions related to the concept of psychological pain and its role in prediction of suicidal behavior remain to be answered in future research. In this narrative review, we have outlined the history of the concept, the definition of psychological pain, and the tools developed for its measurement, summarized the empirical research on psychological pain in relation to suicidal behavior, and suggested future directions for clinical research on psychological pain and suicidal behavior.